Regularization methods for solving the split feasibility problem with multiple output sets in Hilbert spaces - Reich, Simeon; Tuyen, Truong Minh (Topological Methods in Nonlinear Analysis, 2022)
We study the split feasibility problem with multiple output sets in Hilbert spaces.In order to solve this problem, we introduce several new iterative processes by using the Tikhonov regularization method.